2021
DOI: 10.3389/fmicb.2021.645301
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Fermentate-Mediated Reduction of Salmonella Reading and Typhimurium in an in vitro Turkey Cecal Culture Model

Abstract: Salmonella Reading is an ongoing public health issue in the turkey industry, leading to significant morbidity in humans in the United States. Pre-harvest intervention strategies that contribute to the reduction of foodborne pathogens in food animals, such as the yeast fermentation metabolites of Original XPCTM (XPC), may become the key to multi-hurdle farm to fork strategies. Therefore, we developed an anaerobic in vitro turkey cecal model to assess the effects of XPC on the ceca of commercial finisher tom tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Resistance to colonization by Salmonella may be partially attributed to short-chain volatile fatty acid (VFA) and other metabolite products from members of the microbiome, as well as maintenance of gut barrier function and immunity [60]. SCFPs have been shown to increased VFA concentrations for acetate and butyrate and promote favorable shifts in abundance of beneficial taxa and inhibition of Salmonella propagation during challenge [40][41][42]61]. In vivo research has identified immunomodulatory benefits of feeding SCFP to broilers, including those challenged with Eimeria tenella, though no Salmonella-specific mechanisms have been investigated to date [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to colonization by Salmonella may be partially attributed to short-chain volatile fatty acid (VFA) and other metabolite products from members of the microbiome, as well as maintenance of gut barrier function and immunity [60]. SCFPs have been shown to increased VFA concentrations for acetate and butyrate and promote favorable shifts in abundance of beneficial taxa and inhibition of Salmonella propagation during challenge [40][41][42]61]. In vivo research has identified immunomodulatory benefits of feeding SCFP to broilers, including those challenged with Eimeria tenella, though no Salmonella-specific mechanisms have been investigated to date [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the microbiota is directly related to age [ 131 ], and the sooner the microbiota reaches a stable diversity, the sooner the animals are more protected from pathogen invasion [ 132 ] while maximizing the metabolic fermentation and nutrient absorption [ 133 ]. The studies in the literature report a significant effect of YC administration on microbial diversity, indicating that YC might increase diversity and allow the microbiota to stabilize at an earlier age, compared to animals receiving the basal diet only [ 94 , 134 ]. Experiments conducted in vitro, where YC was incubated with the feed and the ceca content of broiler chickens [ 94 , 135 ] or turkeys [ 94 ], resulted in increased alpha and beta diversity, which stabilized over time.…”
Section: Yeast Culturementioning
confidence: 99%
“…The studies in the literature report a significant effect of YC administration on microbial diversity, indicating that YC might increase diversity and allow the microbiota to stabilize at an earlier age, compared to animals receiving the basal diet only [ 94 , 134 ]. Experiments conducted in vitro, where YC was incubated with the feed and the ceca content of broiler chickens [ 94 , 135 ] or turkeys [ 94 ], resulted in increased alpha and beta diversity, which stabilized over time. Changes in the gut microbial diversity due to YC administration in the diet were also confirmed by in vivo studies on aged breeder layers [ 83 ] and broilers [ 91 ].…”
Section: Yeast Culturementioning
confidence: 99%
See 2 more Smart Citations